2004
DOI: 10.1002/bdrb.20027
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of artesunate and an artesunate combination in the rat and rabbit

Abstract: The artemisinins are playing an increasingly important role in treating multidrug-resistant malaria. The artemisinin, artesunate, is currently in use in Southeast Asia and is advocated for use in Africa. In these areas, more than one million people die of malaria each year, with the highest mortality occurring in children and pregnant women. To test the developmental toxicity in ICH-compliant animal studies, embryofetal development studies were conducted in rats and rabbits treated with artesunate alone or a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 41 publications
(43 reference statements)
14
125
1
Order By: Relevance
“…When data were available on more than one species with the same agent, the concordance of responses varied. In the case of artesunate (Clark et al, 2004), both rats and rabbits showed wavy ribs and short/bent long bones. However, in the case of the pesticide S-53482 (Kawamura et al, 1995), rats showed wavy ribs and bent scapulae but rabbits showed no effect.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…When data were available on more than one species with the same agent, the concordance of responses varied. In the case of artesunate (Clark et al, 2004), both rats and rabbits showed wavy ribs and short/bent long bones. However, in the case of the pesticide S-53482 (Kawamura et al, 1995), rats showed wavy ribs and bent scapulae but rabbits showed no effect.…”
Section: Resultsmentioning
confidence: 98%
“…Bent scapulae and shortened and bent long bones (in the absence of gross limb defects) were reported in the presence of wavy ribs in studies conducted in both rats and mice, and in one case in rabbits (Clark et al, 2004). When data were available on more than one species with the same agent, the concordance of responses varied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies showed that ART could inhibit the growth of various carcinoma cell lines [1][2][3] and suppress tumor cell proliferation by inducing apoptosis, 4 indicating that ART may be a promising novel candidate for leukemia therapy. However, a variety of lines of evidence indicate that ART inhibited cell proliferation in a dose-dependent manner, and a high concentration of ART induced embryo toxicity, [5][6][7] reversible renal damage toxicity, 8 and toxicity to bone development, 9 which limit the usefulness of ART. To minimize side effects associated with dosage during chemotherapy, a promising approach is to combine a conventional chemotherapy with new strategies to maximize efficacy of tumor treatment through inducing cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%